Testing Cranial and Spinal Nerve Functional Integrity and Deficits (Out of Print) - Frank Reilly; Edwin Allen; Allison Reed; Jeffrey Altemus (Association of American Medical Colleges, 2008)
Abstract Introduction This virtual patient web-based resource was developed to evaluate diagnostic skills among first-year medical students regarding the cranial nerves as part of peripheral nervous system component of an objective structured clinical exam. It complements didactic and practical (dissection) activities of beginner health professional students enrolled in basic sciences. This courseware was created to stimulate self-directed and problem-based learning. The rationale was to integrate related disciplines into a structured format that is readily accessible for local and distance learning, and learner self-assessment. Methods The user-friendly courseware provides an individual learning module for each of the 12 cranial nerves, and provides learners with opportunities for self-assessment through immediate feedback. A facilitator/users guide is also provided as part of this resource. Results Since implementation of the courseware in 2001, 8% more students score correct answers on our written exam questions. Learner surveys rate the virtual patients, such as this, as the highest among the resources provided for the human structure course. Discussion Organizing content into discrete tutorials is highly effective in teaching learners complex concepts in a simple and interactive manner. It reduces cognitive load and enhances retention. Exposing preclinical students to the initial physical exam through simulations of neurologic deficits provides a glimpse into the comprehensive evaluation of the peripheral nervous system. Framing the deficits in a clinically relevant manner not only serves to solidify what students have learned from their courses, but also creates confidence by demonstrating how they will approach patient problems in their clinical years. Our observations are supported by recent improvements in learner performance on block and subject shelf exams in human structure.